Total-factor energy efficiency in the EU countries - Nela Vlahinić-Dizdarević (Zbornik radova Ekonomskog fakulteta u Rijeci : časopis za ekonomsku teoriju i praksu, 2012)
The purpose of this research is to examine the economy-wide energy efficiency changes in the EU countries in the period from 2000 to 2010 and to compare the results with the traditional energy efficiency indicator. The DEA CCR multiple input-oriented model is applied in order to analyze the efficiency of the use of three inputs (capital stock, labor and energy consumption) in producing GDP as the output. In order to obtain the dynamics of data as to avoid the use of only a single year in calculating energy efficiency the extended DEA method - window analysis - is adopted. The empirical results confirm that the traditional one-factor energy efficiency indicator is too simplifying and could be misleading. The findings on total-factor energy efficiency scores reflect the possibility of substitution among factors in a medium run and changes in the composition of energy use. Projection values of inputs on efficiency frontier identify the amounts of relative inefficiency and, in that context, suggest improvements for all inefficient countries. The results reveal that all inefficient countries could improve their efficiency by reducing some of the inputs.